Credit rationing's determinants of Small and Medium Enterprises (SMEs) in Chittagong, Bangladesh - Mohammed Ziaul Hoque; Nilufar Sultana; Tasmia Thalil (Journal of Global Entrepreneurship Research, 2016)
Small and medium enterprises (SMEs) contribute immensely to Gross Domestic Product (GDP) and they have a significant influence in growth of economy. However, SMEs are constrained in their access to formal credit as financial institutions fail to grant credit due to information asymmetry. This study investigates the credit rationing of SMEs in the city of Chittagong. A sample of 200 firms was selected and analyzed using descriptive statistics and multinomial logit regression. The result suggests that 89 % of the firms obtained loan from microfinance institutions (MFIs). The firms that obtained their loan from banks are 60 % and 48 % of them received the less amount of credit than they desired. In our study, credit rationing was categorized in four types, 24 % of them were unconstrained non-borrowers, 28 % unconstrained borrowers, 19 % quantity rationed and 29 % risk rationed borrowers. Econometrics result shows that education, firm age, marital status, initial outlay, number of employees, and education do not have any impact on credit rationing. On the contrary, age and gender of the owners of the firms, heads of household, status of the living and work place and household size have impact on credit rationing.
Keywords: 650; Credit rationing; Small and medium enterprises; Entrepreneur; Financial institutions; Chittagong; Bangladesh